Nurses' Sociodemographic Background and Assessments of Individualized Care - Idvall, Ewa; Berg, Agneta C.; Papastavrou, Evridiki (My University, 2012)
Aim: The aim of this study was to explore the association between nurses’ characteristics (educational level, country, work title, gender, type of work, age, and length of working experience) and their assessments of individualized care. Design: A cross-sectional comparative survey using questionnaires was employed to sample nurses from seven countries. Methods: Data were collected from orthopedic and trauma nurses from Cyprus, Finland, Greece, Portugal, Sweden, Turkey, and the United States (N = 1,163, response rate 70%) using the Individualized Care Scale-Nurse (ICS-Nurse) and a sociodemographic questionnaire in 2008. Data were analyzed using descriptive statistics and general linear models. Results: When compared with practical nurses, registered nurses, length of working experience, and the country of the nurses were associated with assessments of the support of patient individuality in specific nursing activities (ICS-A-Nurse) and country assessments of individuality in the care provided (ICS-B-Nurse). The background and experience within nursing teams together with the country affect the delivery of individualized care. Conclusions: Overall, our findings suggest that nurses’ personal attributes have important effects on their assessments of individualized nursing care that will be useful when making context-dependent recruitment decisions. Clinical Relevance: The characteristics of nurses contribute to the care delivered in healthcare organizations. Recognition of these nurse-related factors may help nurse leaders in the development and management of clinical practice.
Keywords: Modeling; Nurses